The positioning of prosthetic Margo against gingival Margo, cause or not, of periodontitis - Robo, Ilma; Qafmolla, Ruzhdie; Qyra, Shpetim; Heta, Saimir (International Journal of Dental Research, 2017)
Background: The long, severe contour of prosthetic margo, remnants of cement used for adhesion, these are elements that affect the periodontal status of gingival margo, and then, the care of oral hygiene by the patient, affecting further aggravated gingival infection to fixed further in periodont.Methods: The experiment was conducted in 3 mice, to which were placed metal artificial crowns. It was controlled the effect of the mechanical action of prosthetic margo, established subgingival, agains the marginal gingival tissue.Results: The periodontal status was performed 1 week, 2 weeks, 3 weeks and 1 month later, after placing the crows. After 2 months, was taken the samples of saliva for laboratory, to analyze the bacterial flora in the areas of the presence of gingival margo at the prosthetic crown.Conclusions: The presence of plaque that is not mechanically disconnected from gingival sulcus, influences the periodontal diseases that shows its characteristics, reflected significantly after 7 days, after 14 days, after 21 days. Signs of gingival inflammation are significant features of the evolution of related of periodontal illness, according to these dates already referred to us above.